PENGARUH LAYANAN KONSELING ONLINE TERHADAP PEMENUHAN KEBUTUHAN INFORMASI KESEHATAN MENTAL - Balqis Nurmani Sahara; Heni Nuraeni Zaenudin; Alwan Husni Ramdani (Commed Jurnal Komunikasi dan Media, 2026)
The high prevalence of mental health problems in Indonesia indicates that this issue remains a significant challenge, particularly related to limited and unequal access to mental health services. Telemedicine consultations are becoming increasingly popular and are seen as a solution to improving access to mental health services. This study aims to determine the effect of online counseling services on meeting mental health information needs. This study used a quantitative correlational approach with a survey method and a questionnaire as the instrument. The sample was drawn using a simple random sampling technique, with four hundred respondents who had used online counseling services on the platform. Data analysis was performed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS 4. The results showed that motivation had a significant positive effect on media behavior and user satisfaction. Media behavior significantly influenced the fulfillment of information needs, including information behavior, context, and human condition. Furthermore, user satisfaction also significantly influenced the fulfillment of information needs. Overall, motivation, media behavior, and satisfaction in using online counseling services under the auspices of the Ministry of Health through the platforms Halodoc, Alodokter, Good Doctor, and Naluri significantly influence information behavior, context, and human conditions in meeting mental health information needs.